ANAK DI BAWAH UMUR SEBAGAI WALI NIKAH: SUATU KONSEKUENSI HUKUM DAN URGENSITAS URUTAN PERWALIAN - Hasyim Harun (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2020)
AbstractThis research examines the position of underage children who act as guardians in marriage, by looking at the legal implications and urgency of guardianship hierarchy in fiqh munakahat. The purpose of this study is to strengthen the normative analysis of the absolute position of a guardian in marriage. The method in this research is literature review, with a normative theological approach and descriptive analysis.The findings of this study show that children who are not old enough are not legal guardians in marriage. The legal implication can affect the validity of the marriage. In the urgency of guardianship, underage children may be in the closest position in the guardianship hierarchy, but children who are underage do not fulfill the absolute requirements of a guardian in marriage, so their guardianship rights are automatically terminated.Keywords: Children; Guardian of marriage; Legal Consequences; Trusteeship order.